Current endometriosis care and opportunities for improvement - Charlotte Pickett; Warren G Foster; Sanjay K Agarwal (Reproduction and Fertility, 2023)
Endometriosis is a chronic disease associated with debilitating pain that affects many people assigned female at birth, from menarche through menopause, not just causing pain and infertility but also negatively impacting quality of life, participation in daily activities, productivity, and income. It is associated with increased incidence of obstetric and neonatal complications, anxiety, other chronic diseases, and substantial healthcare costs. Despite the profound negative impact of endometriosis on quality of life, current treatment options remain suboptimal and many patients express dissatisfaction with current care. The prevailing acute-care, single-provider model in which the provider works in relative isolation and thus with limited diagnostic and therapeutic strategies readily available proves inadequate for treating endometriosis. Patients would benefit from earlier diagnosis and referral to a center capable of providing a comprehensive and multimodal management plan that utilizes a chronic care model. Often this can only be achieved through multidisciplinary teams of providers with expertise in endometriosis. The authors acknowledge that many low- and middle-income countries do not have the resources to support such centers but could still benefit from any breakthroughs in treatment they bring about. Researchers need to agree on standardized core outcome measures, relevant to patients with endometriosis and the healthcare system as a whole. Only through increased societal and healthcare provider education and recognition of endometriosis as a chronic disease can we achieve better treatment outcomes.